Description of two new species of the genus Stenothemus from Taiwan (Coleoptera: Cantharidae) - Hsiao, Yun (Zootaxa, 2015)
Two new species of the genus Stenothemus Bourgeois are described from Taiwan, under the names of S. seediq sp. nov. and S. cou sp. nov. Both species are provided with photos of habitus and illustrations of aedeagi, the seventh abdominal ventrites of females, and a distribution map for both the new species is presented. A key for the identification of Stenothemus species from Taiwan is given.